Sequence Analysis of Infectious Bronchitis Virus IS/1494 like Strain Isolated from Broiler Chicken Co-Infected with Newcastle Disease Virus in Egypt During 2012 - Hussein , Hussein A.; Emara, M.M.; Rohaim, M.A.; Ganapathy, K.; Arafa, A.M. (International Journal of Poultry Science, 2014)
In the present study, we characterized IBV field isolate from a vaccinated broiler flock suspected to be co infected Newcastle disease virus (NDV). The flock demonstrated characteristic clinical signs, post mortem lesions and was positive to IBV and NDV by RT-PCR. The (S1) spike glycoprotein gene of (IBV) isolate was partially amplified by RT-PCR, then directly sequenced. The virus was designated (IBV/chicken/Egypt/VRLCU154/2012). Blast analysis, multiple alignments and phylogenetic analysis revealed that IBV isolate was in close relation to the IBV isolate IS/1494/06 (EU780077.2) with high nucleotide homology (97%). The sequence was submitted to NCBI GenBank with the accession No.JX893950. The results of the present study indicate that IS/1494 like strains might have a similar origin based on the genetic relationship among variants and reference strains.